Indisciplina escolar y su incidencia en el proceso de enseñanza aprendizaje de los niños y niñas de la institución de Educación básica Nuestra Señora de la Natividad, del Cantón Quevedo, periodo 2014-2015. Talleres de técnicas disciplinarias. - Castro Pincay, Alexandra Jessenia (2016)
This research developed in the institution of Basic Education "Our Lady of the Nativity", aims to recognize the school indiscipline facing educational institutions and society today. The overall objective of this research is to "assess the impact of school discipline in the process of learning of children. The research aims to improve the disciplinary relationships between students and teachers through the application of disciplinary techniques in the teaching-learning process, enhance the level of student learning and meet the educational standards set by the Ministry of Education which are in force, in educational work. This research requires motivate students, teachers, parents, and community management to implement the practice of values, to strengthen relations of heterogeneous groups, as well as the joint participation of students and teachers in activities in the classroom. The research presents an alternative proposal which is a guide to discipline techniques for teachers and students in order to improve student behavior in the teaching-learning process that takes place in the institution. This is a call to the educational community to encourage the application of participatory techniques in the disciplinary process of meaningful learning.